2013
DOI: 10.1080/10158782.2013.11441518
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, treatment-seeking behaviour and socio-economic impact of malaria in the desert of Rajasthan, India

Abstract: View related articles Citing articles: 1 View citing articles 2013;28(1) South Afr J Epidemiol Infect Original Research: Knowledge, treatment-seeking behaviour and socioeconomic impact of malaria Climate change has resulted in water mismanagement, increased population, urbanisation, industrialisation, poor sanitation and other developmental activities in the desert of Rajasthan. As a consequence, malariagenic conditions have developed and malaria is now a major public health problem in this area. Malaria contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 11 publications
10
13
0
Order By: Relevance
“…Eight studies highlighted socio-economic factors as barriers to malaria control and prevention in SA ( 25 , 29 , 38 , 40 , 47 , 48 , 54 , 55 ). Yadav et al ( 54 ) reported that the majority of people visited government healthcare facilities for blood examination, diagnosis and treatment, as compared to private healthcare facilities. One study, conducted in India, reported that about 51.7% of the participants were aware that governments were taking some initiatives for the prevention and control of malaria ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight studies highlighted socio-economic factors as barriers to malaria control and prevention in SA ( 25 , 29 , 38 , 40 , 47 , 48 , 54 , 55 ). Yadav et al ( 54 ) reported that the majority of people visited government healthcare facilities for blood examination, diagnosis and treatment, as compared to private healthcare facilities. One study, conducted in India, reported that about 51.7% of the participants were aware that governments were taking some initiatives for the prevention and control of malaria ( 31 ).…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies reported that socio-economic factors led to an increase in malaria cases in several parts of SA ( 26 , 27 , 29 , 40 , 48 , 50 , 54 ). Therefore, there has been a clear emphasis that the government should focus on socio-economic factors in order to decrease the adverse effects of socio-economic factor attributes, including climate change, in vulnerability to malaria in this region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients' inappropriate medications practices have been shown to be associated with many factors which could either be intentional or unintentional, complexity of a medication regimen (polypharmacy) and patient's memory, health-care professionals' practices, or even economic reasons among many factors [10][11][12][13]. Considering the established interrelationships between the human behavior-related characteristics such as knowledge, attitudes, and practices (KAP) and their influence on rational management of ailments [14][15][16], evaluation of these patients' behavior-related attributes as it relates to the management of uncomplicated malaria becomes necessary for intervention purposes, especially at the rural communities where majority of the populations are most affected by the disease [6,12,14,17,18]. The present study was mainly to assess patients' KAP toward uncomplicated malaria management in primary health-care (PHC) facilities in Plateau state, Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Studies have shown the influence of patients' knowledge of a disease on their beliefs regarding the aetiology of the disease, 3,4 the seriousness they attached to the ailment 5,6 and their perceptions on the effectiveness of the medication for such ailment. [6][7] Assessing these patients' characteristics during medications might help in the achievement of quality malaria treatment outcomes. Although literatures showed that some Knowledge, Attitude and Practice (KAP) studies have been conducted in Plateau state, Nigeria, the survey instruments might not be reliable and valid because they were not subjected to rigorous validation process to ascertain their reliability and fitness for the study, 3,[8][9][10] hence, validation through statistical test models such as Classical Test Theory (CTT) and Items Response Theory (IRT), also known as Modern Mental Test Theory (MMTT), could be considered an initial step to obtain a test instrument that is both reliable and valid, containing appropriate items for the study.…”
Section: Introductionmentioning
confidence: 99%